2017
DOI: 10.1038/nri.2017.64
|View full text |Cite
|
Sign up to set email alerts
|

The unique immunological and microbial aspects of pregnancy

Abstract: The comparison of the immunological state of pregnancy to an immunosuppressed host-graft model continues to lead research and clinical practice to ill-defined approaches. This Review discusses recent evidence that supports the idea that immunological responses at the receptive maternal-fetal interface are not simply suppressed but are instead highly dynamic. We discuss the crucial role of trophoblast cells in shaping not only the way in which immune cells respond to the invading blastocyst but also how they co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
852
1
20

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 780 publications
(890 citation statements)
references
References 176 publications
17
852
1
20
Order By: Relevance
“…Immune molecules (eg., cytokines and lymphokines) are tightly involved in successful implantation, placentation, fetal growth, and parturition 20. Thus, we cannot make inferences on the role(s) of IFNe regarding reproductive health and pregnancy as results of our study are not generalizable.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Immune molecules (eg., cytokines and lymphokines) are tightly involved in successful implantation, placentation, fetal growth, and parturition 20. Thus, we cannot make inferences on the role(s) of IFNe regarding reproductive health and pregnancy as results of our study are not generalizable.…”
mentioning
confidence: 75%
“…A recent study of 422 pregnant Brazilian women revealed that the placental prevalence of HSV-2 and HSV-1 was 12.6% and 28.0% (maternal side) and 8.3% and 29.9% (fetal side). 20 Prenatal viral infections are hypothesized to alter type I IFN responses to bacteria (commensal or pathogenic) which may lead to adverse pregnancy outcomes. [17][18][19] Type one IFNs have immunomodulatory roles during pregnancy and promote tolerance to the conceptus (fetus and placenta) and protect against infection.…”
mentioning
confidence: 99%
“…After 18 weeks of gestation, the proportion of NK cells is increased in the fetal liver equaling the proportion of T cells 159 . Fetal NK cells are implicated in cytokine- and antibody-mediated NK cell responses in utero; yet, they remain hyporesponsive to HLA class I–negative or allogeneic cells 160 , which could be considered a mechanism for maternal-fetal tolerance 161, 162 . Taken together, these findings suggest that amniotic fluid NK cells could participate in the mechanisms of maternal-fetal tolerance taking place in the fetal compartments.…”
Section: Discussionmentioning
confidence: 99%
“…18 Placental tissues express almost all factors of the immune system. 1,19,20 Among these factors, the placenta produces nitric oxide (NO) in high quantities 21 by nitric oxide synthase, endothelial (EC:1.14.14.47) (eNOS) and nitric oxide synthase, inducible, (EC:…”
mentioning
confidence: 99%